2017
DOI: 10.21273/hortsci11802-17
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Chinese Grape Landraces (Vitis L.) Using Microsatellite DNA Markers

Abstract: In this study, we present the molecular characterization of 61 Chinese grape landraces and 33 foreign cultivars by using nine microsatellite DNA markers. A total of 115 distinct alleles were amplified, and the average allele number was 12.78. The average observed and expected heterozygosity values were 0.797 and 0.839, respectively. The effective allele numbers ranged from 5.011 to 8.575. The average polymorphism information content (PIC) was 0.816. Eighty distinct genotypes were detected, and new syno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…is one of the most economically important fruit crops cultivated and consumed worldwide (OIV, 2018). Vitis has a rich genetic diversity; there are more than 70 species within the genus, with most of the globally important cultivars assigned to Vitis vinifera (Li et al, 2017). Wild Vitis species as well as Muscadinia rotundifolia have been used for hybrid grape breeding as new cultivars and rootstocks, many of which provide resistance to pests and diseases (Carimi et al, 2011;Eibach et al, 2007;Smith et al, 2017).…”
mentioning
confidence: 99%
“…is one of the most economically important fruit crops cultivated and consumed worldwide (OIV, 2018). Vitis has a rich genetic diversity; there are more than 70 species within the genus, with most of the globally important cultivars assigned to Vitis vinifera (Li et al, 2017). Wild Vitis species as well as Muscadinia rotundifolia have been used for hybrid grape breeding as new cultivars and rootstocks, many of which provide resistance to pests and diseases (Carimi et al, 2011;Eibach et al, 2007;Smith et al, 2017).…”
mentioning
confidence: 99%
“…Internationally, France, Germany, Italy, and other countries have used the nine SSR markers to establish a molecular database of grape cultivars (Maul and T€ opfer, 2015), providing an inquiry service for grape research workers. Furthermore, Li et al (2017Li et al ( , 2018 showed that the nine SSR markers can be used to identify the Chinese grape landraces and Euro-American hybrids. = the inbreeding coefficient within subpopulations relative to the total; F is = the inbreeding coefficient within individuals relative to the subpopulation; F it = the inbreeding coefficient within individuals relative to the total.…”
Section: Resultsmentioning
confidence: 99%
“…Klein et al (2018) also used high-throughput sequencing to clarify evolutionary relationships among North American Vitis species. Because SSR markers show high levels of polymorphisms, reproducibility, and codominant inheritance (Aradhya et al, 2013;Li et al, 2017), they have been widely used to study the genetic diversity of grapes (Cao et al, 2020;Guo et al, 2010), sugarcane [Saccharum officinarum (Ali et al, 2019)], wheat [Triticum aestivum (Abbasov et al, 2018)], cabbage [Brassica oleracea (El-Esawi et al, 2016)], and hazelnuts [Corylus heterophylla (Zhao et al, 2020)].…”
mentioning
confidence: 99%
“…In recent years, genomic studies on grapevine cultivars have provided a significant quantity of genomic information, including evolution and domestication processes (Zhou et al, 2019), molecular markers and transferability (Li et al, 2017;Zou et al, 2020), sex determination (Massonnet et al, 2020), and population genetics (Zhou et al, 2019). Furthermore, V. vinifera cultivar genomic information has been utilized as evidence to support ancestral hexaploidization in major angiosperm phyla.…”
Section: Introductionmentioning
confidence: 99%